CAREER DEVELOPMENT CHALLENGES IN STRENGTHENING THE PERFORMANCE OF THE POLRI BAINTELKAM - Michael Bagus Herwasto Nurwicaksono; Chryshnanda Dwilaksana; Payaman Jan Simanjuntak (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
The role of Baintelkam Polri is critically important in maintaining national security stability, identifying and responding to complex and varied security threats. In carrying out its duties, Baintelkam Polri plays a crucial role in gathering information, conducting intelligence analysis, and providing strategic recommendations to support national security policies. However, in the execution of its responsibilities, the Police Baintelkam faces numerous challenges stemming from various aspects, including the rapid advancements in information and communication technology. This technological progress poses a significant challenge to the Police Baintelkam as it opens up new opportunities for cybercriminals and terrorist groups to operate online. Consequently, addressing this threat necessitates more intensive efforts in monitoring and gathering information. The theories employed in this study encompass human resource management, career management, job satisfaction, and SWOT analysis. The research method adopted a qualitative approach, utilizing data collection techniques such as interviews, observations, and data documentation. The findings of this study underscore the pivotal role of career development within the National Police's Security Intelligence Agency (Baintelkam) in enhancing the performance of its members and upholding professionalism in the execution of security intelligence tasks. In an ever-evolving intelligence landscape, career coaching assists members in remaining relevant and effective. Consequently, career development strategies hold significant importance in surmounting challenges and fortifying the performance of the National Police's Security Intelligence Agency (Baintelkam). The overarching objective of career development is to enhance the capabilities, qualifications, motivation, and performance of members, equipping them to address complex and evolving situations in the realm of security intelligence.